Towards Enabling Environmental Social Enterprises: Two Case Studies from Egypt - Kamaly, Rana Emad (AUC Knowledge Fountain, 2026)
Social enterprises (SEs) and environmental social enterprises (ESEs) are emerging as promising potential players in addressing global and Egyptian social and environmental challenges. Operating as a hybrid model of financial sustainability and environmental and social impact, ESEs operate through innovative business models to address community issues, waste management, and resource scarcity through financial sustainability. However, there is a lack of research on ESEs operations, challenges, and the enabling factors that can support their growth and impact. This study explores the enabling factors and challenges affecting ESEs in Egypt through qualitative research, analyzing two case studies from Egypt by conducting semi-structured in-depth interviews with ESE founders, employees, beneficiaries, and customers, in addition to experts in the field of SEs, including donors, academia, corporate social responsibility (CSR) professionals, and other stakeholders. The study findings identified that the enabling factors for ESE’s growth and performance are both external and internal. The external factors include regulatory frameworks, funding access, partnerships, and social and environmental factors. The internal factors include organizational culture (including leadership, culture, and structure), performance measurement systems, and access to markets and technology. The research identifies key obstacles and strategic necessities for enabling and aiding the growth, sustainability, and scalability of ESEs. Based on the interviews with the different stakeholders and the case studies, recommendations are proposed to support the improvement of the ecosystem and internal organizational processes to enable these enterprises to generate sustainable income while addressing Egypt’s socioeconomic and environmental issues. This study contributes to the literature by offering actionable insights to facilitate the growth of this important, promising emerging sector of ESEs, aiming to bridge the limited research on the topic.